UED102: Study Skills - UiTM, Academy of Language Studies (2023)
This course prepares students with learning skills essential for varsity life. It exposes students to basic academic skills; e.g. effective time management, setting goals, learning styles, learning strategies, and processing information from lectures and texts, which would help students cope with academic demands at the tertiary level.